2017
DOI: 10.1371/journal.pone.0182038
|View full text |Cite
|
Sign up to set email alerts
|

Expression of uncharacterized male germ cell-specific genes and discovery of novel sperm-tail proteins in mice

Abstract: The identification and characterization of germ cell-specific genes are essential if we hope to comprehensively understand the mechanisms of spermatogenesis and fertilization. Here, we searched the mouse UniGene databases and identified 13 novel genes as being putatively testis-specific or -predominant. Our in silico and in vitro analyses revealed that the expressions of these genes are testis- and germ cell-specific, and that they are regulated in a stage-specific manner during spermatogenesis. We generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Conversely, because monoclonal antibodies recognize restricted antigenic determinants, it is possible that the monoclonal antibody (RTm01) recognizes the three-dimensional structure of TMCO5 protein so that the antibody could not recognize the protein in the round and differentiated spermatids. However, immunoblotting analysis in Fig 2B as well as that of Kwon et al [17] shows that TMCO5 expression starts from 4 weeks-old and 28-postnatal days, respectively, which indicates that TMCO5 expression starts from elongating spermatids in mice [17, 28, 36]. Taken together, the difference in the expression may be due to the difference in mouse and rat spermatogenesis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Conversely, because monoclonal antibodies recognize restricted antigenic determinants, it is possible that the monoclonal antibody (RTm01) recognizes the three-dimensional structure of TMCO5 protein so that the antibody could not recognize the protein in the round and differentiated spermatids. However, immunoblotting analysis in Fig 2B as well as that of Kwon et al [17] shows that TMCO5 expression starts from 4 weeks-old and 28-postnatal days, respectively, which indicates that TMCO5 expression starts from elongating spermatids in mice [17, 28, 36]. Taken together, the difference in the expression may be due to the difference in mouse and rat spermatogenesis.…”
Section: Discussionmentioning
confidence: 76%
“…Gene Database (Gene ID: 67356, https://www.ncbi.nlm.nih.gov/gene/) confirmed that the expression of the mRNA is restricted in the adult testes and that the deduced amino acid sequence has a coiled-coil domain in the N-terminal region and a transmembrane domain in the C-terminal region with the calculated molecular weight of the protein 35,850. Regarding the expression of the gene, Kwon et al reported the expression of thirteen testis-specific genes including Tmco5 by reverse transcriptase, PCR, and immunoblotting [17]. The function of this gene has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Tex33 is an evolutionary conserved and testis-specific gene. It is transcribed in round spermatids and it does not exist in testicular elongated spermatids and epididymal sperm (Kwon et al, 2017). In this study, we generated a 62bp in frame deletion on Exon2 of Tex33 in C57B/L6 mouse model by using the CRISPR/Cas9 system.…”
Section: Discussionmentioning
confidence: 99%
“…Tex33 is a recently discovered evolutionarily conserved gene present in vertebrates, which is initially expressed in the cytoplasm of round spermatids, and is diminished in elongated spermatids (Kwon et al, 2017). Until now, Tex33 knockout animal model has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The five genes with highest magnitude correlation between pseudotime and the SZS are TPPP2, a gene regulating tubulin polymerization implicated in male infertility 30 , FAM71E1, identified in mouse as testes-predominantly expressed 31 , SPATA42 a long noncoding RNA implicated in azoospermia 32 , MTFR1, a gene regulating mitochondrial fission and MLF1, an oncogene known to be regulated in drosophila testes 33 (Fig. 3A).…”
mentioning
confidence: 99%